2021
DOI: 10.1038/s41586-021-03260-5
|View full text |Cite
|
Sign up to set email alerts
|

A decline in global CFC-11 emissions during 2018−2019

Abstract: The atmospheric concentration of trichlorofluoromethane (CFC-11) has been in decline since the production of ozone-depleting substances was phased out under the Montreal Protocol 1,2. Since 2013, the concentration decline of CFC-11 slowed unexpectedly owing to increasing emissions, probably from unreported production, which, if sustained, would delay the recovery of the stratospheric ozone layer 1-12. Here we report an accelerated decline in the global mean CFC-11 concentration during 2019 and 2020, derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 30 publications
0
80
0
Order By: Relevance
“…In this paper, we set out to derive a predictive model to estimate the contribution of stratospheric trace gas anomalies to surface NH-SH anomalies. We find strong correlations between stratospheric NH and tropospheric NH-SH growth rates in WACCM simulations for and Montzka et al (2021) and Park et al (2021) provide evidence for reduced global and eastern Chinese CFC-11 emissions (respectively) in 2019. Looking forward, our predictive model suggests that in the absence of further anomalous emissions, a new NH-SH positive anomaly should have occurred in 2020, and that negative anomalies can be expected in 2021.…”
Section: Discussionmentioning
confidence: 61%
“…In this paper, we set out to derive a predictive model to estimate the contribution of stratospheric trace gas anomalies to surface NH-SH anomalies. We find strong correlations between stratospheric NH and tropospheric NH-SH growth rates in WACCM simulations for and Montzka et al (2021) and Park et al (2021) provide evidence for reduced global and eastern Chinese CFC-11 emissions (respectively) in 2019. Looking forward, our predictive model suggests that in the absence of further anomalous emissions, a new NH-SH positive anomaly should have occurred in 2020, and that negative anomalies can be expected in 2021.…”
Section: Discussionmentioning
confidence: 61%
“…This grid‐related CFC‐11 emission factor dominated the overall results. However, more recent research has suggested that CFC‐11 emissions are steeply declining, [ 88 ] which suggests that drawing from older studies that include ozone depletion potential may result in overestimates of this impact.…”
Section: The Life Cycle Of Stationary and Vehicle Li‐ion Batteriesmentioning
confidence: 99%
“…Ozone depletion potential, which we briefly touch on, is not likely to be a useful metric to quantify given the ongoing phase‐out of ozone‐depleting substances such as CFC‐11. [ 88 ] Human toxicity does not feature prominently in non‐energy‐related impacts within the studies we surveyed, but as noted earlier, published values regularly rely on data provided by large mining companies [ 86 ] and those datasets likely reflect best industry practices and fail to account for the impact of outliers, particularly in artisanal and small mining operations. Omitting such outliers is a known problem in emissions and environmental impact accounting [ 85 ] and must be mitigated in future LCAs, particularly in the context of material extraction and processing.…”
Section: Recommendations For Battery Lcamentioning
confidence: 99%
“…To improve the climatological profiles especially for the shaving procedure, we retrieved global monthly data for these species from the Halocarbons & other Atmospheric Trace Species (HATS) research program (e.g., Hu et al, 2016;Montzka et al, 2021Montzka et al, , 1996Elkins and Dutton, 2009;Montzka et al, 2009;Conway et al, 1994;Dlugokencky et al, 1994). We further smoothed the data by computing a running mean over twelve consecutive months and fully disregard differences between the hemispheres for simplicity.…”
Section: Appendix E: Standard Atmosphere Profilesmentioning
confidence: 99%